Studies of some genes of Bacillus subtilis MN99 local strains against plant diseases - Saraadanbazar, Ariunaa; Mijidsuren, Byambasuren; Banzragch, Battur (Mongolian Journal of Agricultural Sciences, 2021)
The objective of this study was the isolation and characterization of Bacillus subtilis local strains from the soil in Mongolia. These local strains of B. subtilis are showed to have high antagonistic activities against some plant pathogenic fungi and bacteria. Six strains of B. subtilis were isolated and characterized morphologically, physiologically and biochemically according the Bergey’s Manual of Systematic Bacteriology. In order to identify species of the isolated strains, we amplified and sequenced 16S rRNA gene, essential funtinal genes bmyB, spoVG and srfAA, which are related to antagonistic activity of these strains. The sequences were aligned using CLASTALW multiple sequence alignment tool. Phylogenetic tree was drawn according to Maximum likelihood”method and “Tamura-Nei” model using “MEGA-X version 10.2.6 program. Among all isolates of B. subtilis MN99 and 7/24 strains had higher antagonist activity against plant diseases. According to partial sequence of srfAA (620bp) gene of MN99, the local strain belongs to B. subtilis and partial sequence of bmyB (370bp), spoVG (22bp) gene of MN7/24 strain showed that the it belongs to B. atrophaeus species. All local strains of B. subtilis had bacillomycin synthesis gene, and B. subtilis MN99 strain had only surfactine synthesis gene, while did not have spore formation and hemolysis gene SpoVG.